MELISSOPALINOLOGICAL STUDY OF SOUTHERN BESSARABIA HONEY - ADAMCHUK, LEONORA (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Different natural and climatic zones, directions of agricultural production, ethnic and cultural features of agriculture, and reliefs of the regions of Ukraine are the result of a wide variety of vegetation. Ukraine occupies less than 6% of Europe's area but owns about 35% of all its biodiversity. This leads to a considerable list of plants that are sources of nectar for the production of honey of different varieties. Ukraine produces classic monofloral varieties of honey, such as white acacia, rapeseed, linden, buckwheat, sunflower, as well as less common monofloral, such as mustard, clover, raspberry, bird’s-foot, phacelia, fireweed, goldenrod, sophora, honeydew. Today, regional polyfloral varieties of honey are also produced, such as Carpathian, steppe, Crimean, and other locally produced honey from reserves (for example, from Gomilshansky forests, Mezynsky reserve, Askanian meadows). A common way to identify the botanical and geographical origin of honey and identify its species is to study the pollen composition.This work was aimed to determine the pollen profile of spring honeys of Southern Bessarabia using the method of melissopalynology. Bessarabia is an ethnographic region with its own culture of agricultural production and natural and climatic conditions. The material of the study was samples of honey obtained in the apiaries of the Center for Ethnographic, Green, Rural Tourism, and Family Recreation Frumushika-Nova (Odessa region) in 2021. The pollen profile of honey was investigated using the author's improved method of melissopalynological analysis. Identification of pollen grains was performed using the online database of pollen grains PalDat using a model nutrient medium. The pollen profile of spring honeys of Southern Bessarabia is represented by 30 morphotypes of pollen grains of different plant species, contains honeydew of natural origin and natural impurities (plant particles, wax, bee bodies). In the pollen profile of honey, no dominant (45% or more) pollen grains were detected, secondary – 6, insignificant – 21, inclusions – 3 morphotypes. This allows us to assert the polyflorality of the studied honey with the exception of white acacia, the dominant pollen of which may be 20% or more. Pollen grains of endemic species of steppe plants of Ukraine were found in the pollen profile of spring honeys of Southern Bessarabia (tamarix ramosissima, lathyrus pannonicus, rosa tesquicola, bifora radians, ailanthus altissima, ultus pumila, prunus tenella, viola occulta). The obtained results can be further used to identify the geographical origin of honey from this region. At the next stages of the research, it will be promising to determine the pollen profiles of summer honeys of Southern Bessarabia and other ethnographic regions of Ukraine.
Keywords: melisopalinology; pollen profile; identification; honey; pollen grain